Minat Belajar Peserta Didik terhadap Pembelajaran Biologi Menggunakan Metode Praktikum pada Materi Transpor Membran Sel - Dzuhrotin Adillah; Didi Nur Jamaludin; Achmad Ali Fikri; David Ari Setyawan (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Biology learning is often dominated by a theoretical approach because many theories cause students to feel bored and less interested. The research aims to determine the learning interest of MA Mazro’atul Huda Karanganyar Demak students towards learning biology using practical methods of cell membrane transport material. This type of research uses quantitative descriptive methods. The research subjects were 26 students of class XI MIPA. The data collection technique uses an instrument in the form of a questionnaire which aims to obtain information regarding students’ learning interests. The research data were analyzed by calculating student questionnaire scores, then converted into percentages and interpreted into categories of very good, good, poor, and not good. The research results showed that 74% of students had a fairly good interest in learning while following the biology learning process using the practicum method. The indicator of learning interest with the highest average value is student involvement in biology subjects, namely 81% with a very good category because students are directly involved in the practicum process to work together in organizing, communicating, and interpreting practicum results. The implication is that in biology learning, specifically cell membrane transport material, teachers should use practical methods because it can foster students’ interest in learning.